PENGARUH METODE SNOWBALL THROWING BERBANTUAN MEDIA PAPAN INDIKATOR TERHADAP KEMAMPUAN MENULIS PARAGRAF PADA SISWA SMA 1 JEKULO KABUPATEN KUDUS - Enny Dwi Lestaringingsih; Suhartono -; Catur Karya Agus Priono (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2016)
The study design used the Control Group Pretest-Post-Test with data analysis usingproduct moment correlation formula with rough numbers. The the problems are: How can the problem of media-assisted method of snowball throwing indicator board be applied in writing class? And, how much is influence the media-assisted method of snowball throwing indicator board on writing competence of students? The results of pre-test a hypothesis test on normality test show that x2 hitung = 39.8 for the experimental group and x2 hitung = 23.7 for the control group. If confirmed in x2 tabel = 55.8, then x2 hitung < x2 tabel. The initial values of the two groups are not normally distributed. At the homogeneity test, it shows that Fhitung = 0.913 and Ftabel = 0.578 that Fhitung > Ftabel.. The value of the initial distribution is not homogeneous. Thus, the initial value of the ability of students in both groups is equal. In the experiment class research activities treated media-assisted method of snowball throwing indicator board, while the control group was not given treatment, only using conventional methods. After the post-test was held, the final activity shows that t hitung = 2.631 and t tabel = 1.67 for  = 0.05 ttabel = 2.39  = 0.01. This means t hitung > ttabel for  = 0.05 and  = 0.01.Thus, it can be concluded that the use of snowball throwing method indicator board in writing paragraphs have a significant effect.